Thermal Energy and the Social and Environmental Impacts: Mitigation Alternatives in Thermoelectrics Plants Operation in Brazil | Energia térmica e os impactos sociais e ambientais: alternativas de mitigação na operação de usinas termoelétricas no Brasil - Gabriel, Fabrício Ângelo; Bezerra, Ana Paula Xavier de Gondra; Lorena, Emmanuelle Maria Gonçalves; Santos, Ítala Gabriela Sobral; Silva, Maria Carolina; Moraes, Alex Souza (Revista Geama, 2016)
The Thermoelectrics Plants are progressive development because of population growth and the consequent increase in demand for energy. However, even with all the benefits for the common good, it can become a major villain in the long term, this because of the generation of toxic waste in its maintenance and operation. In this context, it is of paramount importance to analyze and identify the main impacts of the operation of power plants. The present work had for finality conduct a comprehensive literature review in order to raise the main social and environmental impacts and possible ways to mitigate. It notes that the social and environmental impacts of these projects are immeasurable, being that, mostly, these impacts are unknown and interfere directly and/or indirectly in the local population, flora and fauna, without the necessary protective measures. That way, considered boastful concentration of efforts to develop innovative methods to generate electricity and create more favorable conditions to existing methods. Together, establish means low cost in operation and minimize the impacts resulting from these processes, whether social or environmental.